2014
DOI: 10.2147/cia.s65448
|View full text |Cite
|
Sign up to set email alerts
|

N-palmitoylethanolamine and N-acetylethanolamine are effective in asteatotic eczema: results of a randomized, double-blind, controlled study in 60 patients

Abstract: BackgroundAsteatotic eczema (AE) is characterized by itchy, dry, rough, and scaling skin. The treatments for AE are mainly emollients, usually containing urea, lactic acid, or a lactate salt. N-palmitoylethanolamine (PEA) and N-acetylethanolamine (AEA) are both endogenous lipids used as novel therapeutic tools in the treatment of many skin diseases. The purpose of this study was to compare a PEA/AEA emollient with a traditional emollient in the treatment of AE.MethodsA monocentric, randomized, double-blind, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 23 publications
1
59
0
1
Order By: Relevance
“…It has been shown that the NAE pathway can be manipulated using receptor agonists/antagonists, or by applying enzyme inhibitors to alter NAE metabolism, for example inhibitors of fatty acid amide hydrolase may be a useful treatment for dry skin . Further, topical treatments, including PEA, have proven an effective eczema treatment and merit investigation in ICD …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the NAE pathway can be manipulated using receptor agonists/antagonists, or by applying enzyme inhibitors to alter NAE metabolism, for example inhibitors of fatty acid amide hydrolase may be a useful treatment for dry skin . Further, topical treatments, including PEA, have proven an effective eczema treatment and merit investigation in ICD …”
Section: Discussionmentioning
confidence: 99%
“…In the skin, the endocannabinoid system plays a regulatory role in proliferation, differentiation and cytokine release (59). Incorporation of an endocannabinoid-targeting component within a cream, such as N-palmitoylethanolamine, can decrease the sensation of itch by increasing the lipid content in the barrier (18,60,61).…”
Section: Emollientsmentioning
confidence: 99%
“…We sought to improve SC moisturization using novel semi‐occlusive barrier mimetic lipids together with humectants and to mitigate skin redness using this moisturizer formulation supplemented with the anti‐inflammatory agents panthenol, PEA and NAM. The latter was also added for their likely effects on improving keratinocyte differentiation and also boosting cellular NAD levels with NAM.…”
Section: Discussionmentioning
confidence: 99%
“…While reducing the negative effects of UV irradiation is key in alleviating sensitive skin symptoms, maintaining adequate moisturization is also important . Formulations that contain lamellar lipid bilayers, mimicking those found within the SC, are known to be more effective clinically than non‐lamellar lipid formulations in treating dry skin and uremic pruritus in addition to improving barrier function and erythema in subjects with sensitive skin and atopic eczema . The non‐physiological lipid, isostearyl isostearate (ISIS), has also been shown to positively influence lipid lamellar phase behaviour in experimental skin barrier and lipid models .…”
Section: Introductionmentioning
confidence: 99%